2009
DOI: 10.1002/jmv.21688
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory cytokines determine the outcome of Japanese encephalitis virus infection in mice

Abstract: Japanese encephalitis virus (JEV) induces an acute infection of the central nervous system, the pathogenic mechanism of which is not fully understood. To investigate host response to JEV infection, 14-day-old mice were infected via the extraneural route, which resulted in encephalitis and death. Mice that received JEV immune splenocyte transfer were protected from extraneural JEV infection. Pathology and gene expression profiles were then compared in brains of mice that either succumbed to JEV infection or wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…CSF IL-6 and IL-10 levels were significantly higher in non-JE cases compared with JE cases. Significantly higher levels of IL-10 in non-JE patients compared to JE patients have also been observed by Kalita et al and Pandey et al (19,27). High IL-10 levels in the non-JE group could be related with the protective response seen early in the course of infection, which may contribute to the decreased severity of disease and enhanced survival observed in non-JE patients.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…CSF IL-6 and IL-10 levels were significantly higher in non-JE cases compared with JE cases. Significantly higher levels of IL-10 in non-JE patients compared to JE patients have also been observed by Kalita et al and Pandey et al (19,27). High IL-10 levels in the non-JE group could be related with the protective response seen early in the course of infection, which may contribute to the decreased severity of disease and enhanced survival observed in non-JE patients.…”
Section: Discussionsupporting
confidence: 58%
“…The anti-inflammatory nature of IL-10 is well known. Biswas et al investigated the host response to JE infection in mouse models and showed that mice with increased production of IL-10 had a reduced expression of the pro-inflammatory cytokine interferon gamma (IFN-γ) and hence better survival (19). The protective effect of IL-10 in tick-borne encephalitis was shown in a recent study by Tun et al where IL-10 knockout mice were seen to have a higher mortality after infection with the Oshima strain of tick-borne encephalitis (20).…”
Section: Discussionmentioning
confidence: 99%
“…The neuroinvasive form of JEV infection is characterized both by neuronal death and the activation of resident glial cells as well as the infiltration of mononuclear effector cells, whose activities promote both viral clearance and neuronal injury (German et al, 2006;Ghoshal et al, 2007;Ravi et al, 1997). Accumulating evidence shows that an antiinflammatory strategy is beneficial against JEV-associated neuronal death and encephalitis (Biswas et al, 2010;Mishra and Basu, 2008). Thus, neurons may be destroyed by a variety of direct and indirect mechanisms including JEV-or cytokine-mediated cytotoxicity.…”
Section: Introductionmentioning
confidence: 98%
“…JEV neuropathogenesis is thought to be largely an outcome of the unregulated inflammatory response of the host neuronal immune system. In particular, an increased expression of IL-10 and reduced synthesis of IFN-c, STAT1 and STAT2 correlate with better survival in mice (Biswas et al, 2010). However, damage to neuronal tissue is an outcome of host cell death by direct virus infection and that induced by the proinflammatory factors (Ghoshal et al, 2007;Swarup et al, 2007).…”
mentioning
confidence: 99%